Tolerability of Nasal Delivery of Humidified and Warmed Air at Different Temperatures: A Randomised Double-Blind Pilot Study - Bibby, Susan; Reddy, Sumeet; Cripps, Terrianne; McKinstry, Steve; Weatherall, Mark; Beasley, Richard; Pilcher, Janine (Pulmonary Medicine, 2016)
Objectives. Delivery of warmed, humidified air via nasal high flow therapy could potentially reduce replication of temperature-sensitive viruses in the upper respiratory tract. This study investigates whether nasal high flow therapy is well tolerated by healthy adults at 37°C and 41°C. Methods. In this randomised, double-blind, controlled crossover pilot trial, nasal high flow therapy was used to deliver humidified air at 35 L/min, at either 37°C or 41°C, for three one-hour sessions of use over one day. The alternative was delivered at least 14 days later. Ten healthy, nonsmoking adults were asked, via questionnaire after each day’s use, whether they would use nasal high flow therapy while being unwell with a cold or flu if it was demonstrated to improve symptoms. Results. All participants completed both interventions. Eighty percent responded “yes” to future use of nasal high flow therapy, for both 37°C and 41°C. There was no significant change from baseline in saccharin times following either intervention or in the following morning. Conclusions. Delivering humidified air via nasal high flow therapy at both 37°C and 41°C is well tolerated by healthy adults. This supports investigation into the potential use of nasal high flow therapy as treatment in viral upper respiratory tract infections. Trial Registration. This trial is registered with ACTRN12614000183684 (tolerability study of nasal delivery of humidified & warmed air).